The impact of the First World War on the poetry of Wilfred Owen - Mahmud, Mohammad Riaz (IIUC Studies, 2009)
In 1914 the First World War broke out on a largely innocent world, a world that still associated warfare with glorious cavalry charges and the noble pursuit of heroic ideals. This was the world's first experience of modern mechanized warfare. As the months and years passed, each bringing increasing slaughter and misery, the soldiers became increasingly disillusioned. Many of the strongest protests made against the war were made through the medium of poetry by young men horrified by what they saw. They not only wrote about the physical pain of wounds and deaths, but also the mental pain that were consequences of war. One of these poets was Wilfred Owen. In his poetry we find the feelings of futility, horror, and dehumanization that he encountered in war. doi: 10.3329/iiucs.v4i0.2689 IIUC STUDIES Vol. - 4, December 2007 (p 25-40)